All-Cause and Acute Pancreatitis Health Care Costs in Patients With Severe Hypertriglyceridemia. Issue 1 (January 2017) - Rashid, Nazia; Sharma, Puza P.; Scott, Ronald D.; Lin, Kathy J.; Toth, Peter P.
Abstract : Objective: The aim of this study was to assess health care utilization and costs related to acute pancreatitis (AP) in patients with severe hypertriglyceridemia (sHTG) levels. Methods: Patients with sHTG levels 1000 mg/dL or higher were identified from January 1, 2007, to June 30, 2013. The first identified incident triglyceride level was labeled as index date. All-cause, AP-related health care visits, and mean total all-cause costs in patients with and without AP were compared during 12 months postindex. A generalized linear model regression was used to compare costs while controlling for patient characteristics and comorbidities. Results: Five thousand five hundred fifty sHTG patients were identified, and 5.4% of these patients developed AP during postindex. Patients with AP had significantly ( P < 0.05) more all-cause outpatient visits, hospitalizations, longer length of stays during the hospital visits, and emergency department visits versus patients without AP. Mean (SD) unadjusted all-cause health care costs in the 12 months postindex were $25, 343 ($33, 139) for patients with AP compared with $15, 195 ($24, 040) for patients with no AP. The regression showed annual all-cause costs were 49.9% higher ( P < 0.01) for patients with AP versus without AP. Conclusions: Patients who developed AP were associated with higher costs; managing patients with sHTG at risk of developing AP may help reduce unnecessary costs.